Comparative fecal microbiome analysis of the endangered Volcano rabbit (Romerolagus diazi) reveals a microbial core in contrasting habitats of Central Mexico - Leslie M. Montes-Carreto; Hanya D. Arellano-Hernández; José Antonio Guerrero; Esperanza Martinez-Romero (PLoS ONE, 2026)
Herbivores show a larger microbial diversity in their guts than omnivores or carnivores. Bacterial symbionts expand the host digestion capacity by fermenting cellulose and hemicellulose. Comparisons between populations in different distribution areas can reveal how environmental conditions affect microbiota, helping to design conservation strategies. The Volcano rabbit ( Romerola gus diazi ) is the smallest lagomorph in Mexico. It is classified as endangered by Mexican legislation and as critically endangered by the IUCN, in the Red List. Here we extend our previous microbiome study to another region in Mexico from a high site near an active volcano, the Popocatépetl. In both areas, the most abundant bacterial genera included Acinetobacter , Enterobacter , Streptomyces , Bacteroides , Pseudomonas , Janthinobacterium , Flavobacterium , and Duganella . Among Archaea, Methanosarcina , Halobaculum , Thermococcus , Halorubrum , and Methanobrevibacter were prevalent. Fungal genera such as Fusarium , Ascochyta , Pyricularia , Aspergillus , and Colletotrichum were also identified. Potential functions were identified including carbohydrate, amino acid and nucleotide metabolism. The most abundant enzymes were transferases, hydrolases and oxidoreductases. The PERMANOVA test between areas for Bacteria (p = 0.26), Archaea (p = 0.21) and Fungi (p = 0.48) indicated no significant differences in the taxonomic composition or coding sequences (p = 0.5), although there were differences in relative abundances. Additionally, for archaea, genera that had not been reported previously in Volcano rabbit fecal microbiomes such as Halomicroarcula , Halomicrobium , Haloplanus , and Sulfolobus were identified, with Sulfolobus found exclusive in Izta-Popo. The Volcano rabbit fecal microbiome showed unique bacterial and archaeal profiles. Overall, these microbial communities are likely to contribute to the digestion of plant fibers, phenolic compounds, and other dietary components, underscoring their importance for the health and conservation of these endangered species.